Association of Body Mass Index to Onset of Puberty in Male - Subramaniam, Jeevithaambigai; Sofiatin, Yulia; Fadil, R.M. Ryadi (Althea Medical Journal, 2016)
Background: Puberty is the period where the developmental process takes place, marks the transition from childhood to adulthood with physical and physiological changes. This study was conducted to discover association between body mass index (BMI) and onset of puberty in male.Methods: A cross-sectional study was conducted from May to November 2013 using simple random sampling which was part of bigger research study by Nutrition and Metabolism Working Group on Jatinangor Cohort, especially Puberty Survey in Jatinangor, by Department of Epidemiology and Biostatistics Faculty of Medicine Universitas Padjadjaran. Respondents were 286 males, 9â15 years old from Elementary School (Sekolah Dasar/SD) and Junior High School (Sekolah Menengah Pertama/SMP). Inclusion criteria were students who are healthy at the time and do did not have obvious disease, attained puberty within 1 year or did not yet attained it, and voluntarily followed the study procedure. The questionnaire was provided after getting informed consent from the respondents. The data analysis was done conducted using Pearson Correlation. Results: The magnitude of association of BMI to the onset of puberty in male among school students in Jatinangor was 0.243 which showed there was positive correlation coefficient between BMI to onset of puberty in male. Test results with the t-test showed t-value of 2.683 with p-value of 0.008.Conclusions: There is association of BMI to the onset of puberty in male among school students in Jatinangor. Positive correlation indicates that the higher the BMI, the faster the onset of puberty in male. [AMJ.2016;3(1):12â16]Â DOI:Â 10.15850/amj.v3n1.697